:) Brainliest pls?
Answer:
f(x) * g(x) = -35x^3 - 59x^2 - 74x - 72
Step-by-step explanation:
If f(x) = 7x+9 ang g(x) = -5x^2 - 2x - 8, then
f(x) * g(x) will be:
(7x+9)(-5x^2 - 2x -8)
f(x) * g(x) = -35x^3 - 59x^2 - 74x - 72
38/14= 2 10/14= 2 5/7
The answer is 2 5/7
Answer:
x = 2.
Step-by-step explanation:
5[3(x + 4) − 2(1 − x)] − x − 15 = 14x + 55
5[3x + 12 - 2 + 2x] - x - 15 = 14x + 55
5[5x + 10] - x - 15 = 14x + 55
25x + 50 - x - 15 = 14x + 55 Now we subtract 14x from both sides:
25x + 50 - x - 15 - 14x = 14x - 14x + 55
10x + 50 - 15 = 55 Now we subtract 50, add 15 to both sides:
10x + 50 - 50 - 15 + 15 = 55 - 50 + 15
10x = 20
x = 2.
Answer:
8x-14=8x-14
Step-by-step explanation:
So if both the equations are the same, that means that any value of x put in the equation will equal itself, so that means that there are infinite solutions to the equation
If you try to solve this equation, this happens
8x-14=8x-14
add 14 to both sides
8x=8x
divide by 8 both sides
x=x
This means that there are infinite solutions because any number could be x and it would still work